THE USE OF THEME-BASED TEACHING TO IMPROVE THE STUDENTS' WRITING SKILLS IN SMKN 5 SELAYAR: A PRE-EXPERIMENTAL RESEARCH - Noviyanti, Adelina; Nunung Anugrawati; Azis, Awalia (English Language Teaching Methodology, 2023)
This research aims to find out the use of theme-based teaching in improving the students’ writing skills in SMKN 5 SELAYAR.This research was pre-experimental research using quantitative design in analyzing the data. The instrument used was writing test which contain pre-test, treatments and post-test. The population was tenth grade of SMKN 5 SELAYAR students and the sample was X. FAR class that was selected by using purposive sampling technique. Based on the results of the research, it is found that the use of theme-based teaching can improve students' writing skills in terms of content, vocabulary and grammar in the form of descriptive text in class X FAR SMKN 5 SELAYAR. This is evidenced by the results of the students' scores. It can be seen from the average value of students that there is an increase of 21.1%. The pre-test was 67.03 which classified as good enough category and the post-test was 81.17 which classified as great category, the post-test score was higher than the pre-test. In addition, t-test value higher than the t- table value (12.415>1.699). It means that there is an improvement by using of theme-based teaching to improve the student' writing skills in descriptive text.